Orbital angular momentum density of a general Lorentz–Gauss vortex beam. (24th June 2016) - Zhou, Guoquan; Ji, Zhiyue; Ru, Guoyun
Abstract: Based on the vectorial Rayleigh–Sommerfeld integral formulae, the analytical expression of a general Lorentz–Gauss vortex beam with an arbitrary topological charge is derived in free space. By using the analytical expressions of the electromagnetic field beyond the paraxial approximation, the orbital angular momentum density of a general Lorentz–Gauss vortex beam can be calculated. The effects of the linearly polarized angle and the topological charge on the three components of the orbital angular momentum density are investigated in the reference plane. The two transversal components of the orbital angular momentum are composed of two lobes with the same areas and opposite signs. The longitudinal component of the orbital angular momentum density is composed of four lobes with the same areas. The sign of the orbital angular momentum density in a pair of lobes is positive, and that of the orbital angular momentum density in the other pair of lobes is negative. Moreover, the negative magnitude of the orbital angular momentum density is larger than the positive magnitude of the orbital angular momentum density. The linearly polarized angle affects not only the shape and the location of the lobes, but also the magnitude of the three components of the orbital angular momentum density. With increasing the topological charge, the distribution of the orbital angular momentum density expands, the magnitude of the orbital angular momentum density increases, and the shape of the lobe also slightly changes.